2020
DOI: 10.1111/rda.13735
|View full text |Cite
|
Sign up to set email alerts
|

BMP‐15 activity on in vitro development of collared peccary (Pecari tajacu Linnaeus, 1758) preantral follicles

Abstract: This study investigated the effects of BMP‐15 on the in vitro development of preantral follicles of collared peccaries. Ovarian fragments were cultured for 1 or 6 days in Tissue Culture Medium 199 (TCM199+) supplemented with BMP‐15 at rates of 0, 1, 25 or 50 ng/ml. The fragments were analysed histologically by evaluating follicular morphology, activation and growth as well as the potential for proliferation of granulosa cells. Our results show the addition of 25 ng/ml BMP‐15 in the medium provided the greatest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“… Gomes et al (2020) confirmed that the addition of 25 ng/mL of BMP-15 to the culture medium of collared peccary PAFs maintained a high number of morphologically healthy follicles and stimulated the activation of primordial follicles after 6 days in culture. In 2021, Campos et al observed that GDF-9, especially at a 200 ng/mL inclusion in the culture medium, was actively involved in the in vitro development of collared peccary PAFs.…”
Section: Preservation and Use Of Ovarian Tissuessupporting
confidence: 57%
“… Gomes et al (2020) confirmed that the addition of 25 ng/mL of BMP-15 to the culture medium of collared peccary PAFs maintained a high number of morphologically healthy follicles and stimulated the activation of primordial follicles after 6 days in culture. In 2021, Campos et al observed that GDF-9, especially at a 200 ng/mL inclusion in the culture medium, was actively involved in the in vitro development of collared peccary PAFs.…”
Section: Preservation and Use Of Ovarian Tissuessupporting
confidence: 57%
“…It has been shown to be essential for oocyte development, ovulation rate, fertilization, and embryonic competence [ 56 ]. The treatment of collared peccary preantral follicles with BMP-15 stimulated the activation of primordial follicles and maintained a high number of morphologically healthy follicles [ 57 ]. Some breeds, such as sheep, are carriers of important genetic variants in the ovulation rate.…”
Section: Bmps Signaling In Female Reproductive Systemmentioning
confidence: 99%
“…Probably, other supplements need to compose the PAF culture media so that follicular activation can be observed in red-rumped agouti. This encouraging results present the perspective of improving the IVC system by trying other media as the MEM + ( Lima et al, 2018 ), other additives like the growth factors as the bone morphogenic protein 15 [BMP-15; Gomes et al (2020) ] or the growth differentiating factor-9 [GDF-9; Campos et al (2021) ], long-term culturing procedures ( Choi et al, 2008 ), culturing isolate PAFs ( Jamalzaei et al, 2016 ), and the use of three-dimensional systems ( Asgari et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%